Clinical Differentiation of Upper Extremity Pain Etiologies. Issue 8 (August 2015) - Ponnappan, Ravi K.; Khan, Mustafa; Matzon, Jonas L.; Sheikh, Emran S.; Tucker, Bradford S.; Pepe, Matthew D.; Tjoumakaris, Fotios P.; Nassr, Ahmad N.
<x xml:space="preserve">Abstract</x> Upper extremity pain can result from many overlapping etiologies. These can be categorized into anatomic regions and specific organ systems. Anatomically, pain etiologies are classified into four major groups: neurologic, musculoskeletal, vascular, and other (eg, tumor, infection). Knowledge of the characteristic clinical presentation and physical examination findings of each group can help distinguish the source of the patient's complaints quickly so that an accurate clinical diagnosis can facilitate appropriate diagnostic measures and treatment. A focus on the neurologic causes of upper extremity pain (ie, cervical spine pathology, peripheral nerve compression, neuropathy) and musculoskeletal causes of shoulder and elbow pain (eg, adhesive capsulitis, calcific tendinitis, biceps tendinitis, synovitis) and the distinguishing characteristics (eg, periscapular pain, two-point discrimination, signal intensity on T2-weighted MRI) helps determine the appropriate diagnosis.